In Situ Expansion, Differentiation, and Electromechanical Coupling of Human Cardiac Muscle in a 3D Bioprinted, Chambered Organoid. Issue 2 (3rd July 2020) - Kupfer, Molly E.; Lin, Wei-Han; Ravikumar, Vasanth; Qiu, Kaiyan; Wang, Lu; Gao, Ling; Bhuiyan, Didarul B.; Lenz, Megan; Ai, Jeffrey; Mahutga, Ryan R.; Townsend, DeWayne; Zhang, Jianyi; et al.
Abstract : Rationale: One goal of cardiac tissue engineering is the generation of a living, human pump in vitro that could replace animal models and eventually serve as an in vivo therapeutic. Models that replicate the geometrically complex structure of the heart, harboring chambers and large vessels with soft biomaterials, can be achieved using 3-dimensional bioprinting. Yet, inclusion of contiguous, living muscle to support pump function has not been achieved. This is largely due to the challenge of attaining high densities of cardiomyocytes—a notoriously nonproliferative cell type. An alternative strategy is to print with human induced pluripotent stem cells, which can proliferate to high densities and fill tissue spaces, and subsequently differentiate them into cardiomyocytes in situ. Objective: To develop a bioink capable of promoting human induced pluripotent stem cell proliferation and cardiomyocyte differentiation to 3-dimensionally print electromechanically functional, chambered organoids composed of contiguous cardiac muscle. Methods and Results: We optimized a photo-crosslinkable formulation of native ECM (extracellular matrix) proteins and used this bioink to 3-dimensionally print human induced pluripotent stem cell–laden structures with 2 chambers and a vessel inlet and outlet. After human induced pluripotent stem cells proliferated to a sufficient density, we differentiated the cells within the structure and demonstrated function of the resultant human chambered muscle pump. Human chambered muscle pumps demonstrated macroscale beating and continuous action potential propagation with responsiveness to drugs and pacing. The connected chambers allowed for perfusion and enabled replication of pressure/volume relationships fundamental to the study of heart function and remodeling with health and disease. Conclusions: This advance represents a critical step toward generating macroscale tissues, akin to aggregate-based organoids, but with the critical advantage of harboring geometric structures essential to the pump function of cardiac muscle. Looking forward, human chambered organoids of this type might also serve as a test bed for cardiac medical devices and eventually lead to therapeutic tissue grafting. Abstract : Supplemental Digital Content is available in the text.